Evaluation of injury rates in soccer players before, during, and after the COVID-19 pandemic - My, G.; Farì, G.; Muscella, A.; Marsigliante, S. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study aimed to evaluate injury rates among Serie A soccer players across three seasons, highlighting the impact of the COVID-19 pandemic.